PENGARUH PENATAAN FORMASI TEMPAT DUDUK TERHADAP MOTIVASI BELAJAR ANAK DI TK ISLAM SULTHONIYAH SAMBAS TAHUN PELAJARAN 2020-2021 - Sterfebrian (CV. ADIBA AISHA AMIRA, 2023)
Children's learning motivation in the arrangement of the letter U seating formation at the Sulthoniyah Sambas Islamic Kindergarten for the 2020-2021 Academic Year. Children's learning motivation in the arrangement of traditional letter seating formations at the Sulthoniyah Sambas Islamic Kindergarten for the 2020-2021 Academic Year. There is a significant influence between the arrangement of seating formations on children's learning motivation in Sulthoniyah Sambas Islamic Kindergarten for the 2020-2021 Academic Year. The population in this study amounted to 29 children, with a sample of 20 children. The approach used in this research is quantitative, with the type of comparative research and the method used is experimental. Data collection techniques using direct observation techniques and documentation techniques. The data analysis technique is calculated using IBM SPSS Statistics Ver.23. The 1st and 2nd sub-problems were answered using a descriptive test of central tendency (central symptoms), while the 3rd sub-problem was answered using the Mann Withney U Test. The results showed that: Children's learning motivation is high in the arrangement of the letter U seating formation in Sulthoniyah Islamic Kindergarten for the 2020-2021 academic year with an average learning outcome (mean) of 27.40. Children's learning motivation is high in the arrangement of traditional letter seating formations at Sulthoniyah Sambas Islamic Kindergarten for the 2020-2021 Academic Year with an average learning outcome (mean) of 19.40. There is a significant influence between the arrangement of seating formations on children's learning motivation in Sulthoniyah Sambas Islamic Kindergarten for the 2020-2021 Academic Year. Based on the results of the Mann Withney U Test, it was concluded that the value of Z = -3.569 and Asymp. Sig. (2-tailed) = 0.00 < 0.05, Ha is accepted and H0 is rejected. There is a significant difference in the letter U seating formation, which is higher in the mean rank of 15.20 than the traditional letter seating formation, namely the mean rank 5.80, the difference in distance between the two is 9.4.